Seismic Vulnerability Assessment of Masonry and RC Building Stocks: A Simplified Methodology - Francesca Ferretti; Claudio Mazzotti; Marco Savoia (Buildings, 2024)
Assessing the seismic vulnerability of existing buildings at the territorial scale is a crucial aspect for seismic-prone regions to properly plan effective strategies for disaster risk management. This paper presents a simplified methodology for the seismic vulnerability assessment of existing masonry and reinforced concrete buildings. The main purpose is to provide a tool able to evaluate the vulnerability of large building stocks, with the aim of defining priorities for further investigations or interventions. The procedure, inspired by methods in the literature devoted to the large-scale evaluation of structural vulnerability, allows defining the collapse peak ground acceleration (PGAc) through the evaluation of the resisting shear force, the latter being estimated by mechanical considerations and by taking expert judgment into account to consider the real structural complexities involved. A classification is proposed, which aims to categorize buildings within homogenous groups characterized by a level of seismic vulnerability belonging to given intervals. The method was calibrated with reference to several case studies in order to reach a sufficient level of reliability in the vulnerability estimate and was then applied to a significant number of school buildings in the province of Ravenna, Italy. For some of them, the simplified methodology was validated through comparisons with results obtained by means of vulnerability assessment procedures based on finite element analyses.